ABSURDISME PELUKIS DAN WANITA KARYA ADHYRA IRIANTO - lusi Handayani; Sahrul N; Roza Muliati (Grenek: Jurnal Seni Musik, 2020)
This study aims to reveal the absurdism value contained in the show Pelukis dan Wanita by Adhyra Irianto. This study uses a descriptive analysis approach with qualitative research methods. The theoretical framework chosen to answer the research questions is the concept of dramatic structure and the concept of absurdism. Several conclusions resulted from this research, namely, Pelukis dan Wanita by Adhyra Irianto has an indication of absurdism from play texts to performance texts. Painters and Women have plots that are not circular or circular, conflicts without certainty, unbalanced characters and unresolved ending. The indications of absurdism depicted in this work are irregularity, uncertainty and imbalance.